2016
DOI: 10.5194/soil-2016-13
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Morphological dynamics of gully systems in the sub-humid Ethiopian Highlands: The Debre Mawi watershed

Abstract: Abstract. Gully expansion in the Ethiopian highlands dissects vital agricultural lands with the eroded materials adversely impacting downstream resources, for example as they accumulate in reservoirs. While gully expansion and rehabilitation have been more extensively researched in the semi-arid region of Ethiopia, few studies have been conducted in the (sub) humid region. For that reason, we assessed the severity of gully erosion and identified gully-forming processes in 13 selected permanent gullies in the s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Sediment concentrations and loads decreased greatly in both watersheds after the implementation of conservation measures (Figure 7b,c). In the Debre Mawi watershed [22,28,48,49], in cases where gullies were not treated, we found that the sediment concentration at the outlet did not decrease after the installation of upland conservation practices because the unconsolidated soil in the gullies added the sediment back into the water that was taken out by the upland practices. Here, gullies were treated (Table 2) and sediment concentration decreased because gullies are the major sources of sediment [50][51][52].…”
Section: Overall Impact Of Soil and Water Conservation On Hydrologicamentioning
confidence: 77%
See 2 more Smart Citations
“…Sediment concentrations and loads decreased greatly in both watersheds after the implementation of conservation measures (Figure 7b,c). In the Debre Mawi watershed [22,28,48,49], in cases where gullies were not treated, we found that the sediment concentration at the outlet did not decrease after the installation of upland conservation practices because the unconsolidated soil in the gullies added the sediment back into the water that was taken out by the upland practices. Here, gullies were treated (Table 2) and sediment concentration decreased because gullies are the major sources of sediment [50][51][52].…”
Section: Overall Impact Of Soil and Water Conservation On Hydrologicamentioning
confidence: 77%
“…Once the rills have formed, sediment concentrations decrease. When gullies are present downstream, any decrease in sediment is negated by unconsolidated sediments of the slipping banks that can easily be picked up by the flowing water in the gullies [48,49]. Under these circumstances, the peak sediment concentrations remain elevated throughout the rain phase, as seen in the Tikur-Wuha and the Guale watersheds, especially in 2010 before gully rehabilitation practices were in place (Figure 7a).…”
Section: Overall Impact Of Soil and Water Conservation On Hydrologicamentioning
confidence: 84%
See 1 more Smart Citation
“…The red rectangle is the location of Debre Mawi watershed. (b) Gully network in the Debre Mawi watershed in 2013 estimated as about 20 ha (Zegeye et al, ), the red rectangle shows the gully studied. (c) Photograph of the Debre Mawi watershed with the valley bottom lands in the middle of the picture, where the gullies are developing.…”
Section: Methodsmentioning
confidence: 99%
“…The study site is a sub‐watershed within the Debre Mawi watershed, in the northwestern part of the country (Figure ), which encompasses a total area of 523 ha and is located 30 km south of the city of Bahir Dar at 37°22′ east and 11°18′ north (Tilahun et al, ). This study site was selected because of its strategic importance for local crops ( Eragrostis tef ) and climatic representativeness (in the sub‐humid highlands), to contribute to ongoing research (Tebebu et al, ; Tilahun et al, ; Dagnew et al, ; Zegeye et al, ), and because of logistical partnerships with local research organizations. Slopes range between 1% and 30%, and the watershed is underlain by a shallow highly weathered and fractured basalt with compacted clays overlain (Tilahun et al, ).…”
Section: Methodsmentioning
confidence: 99%